1988
DOI: 10.1203/00006450-198804000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Naloxone Potentiates Epinephrine Release during Hypoxia in Fetal Sheep: Dose Response and Cardiovascular Effects

Abstract: The effect of opiate receptor blockade on the plasma catecholamine response to hypoxemia was studied in seven chronically catheterized fetal lambs in utero. All animals underwent treatment with hypoxia alone, naloxone infusion alone (2 mg/kg) and hypoxia with naloxone at four different dosages (0.1, 0.5, 1.0, and 2.0 mg/kg). Maternal and fetal hypoxia was maintained for 20 min. There were no differences noted in the degree of hypoxemia or acidemia between the different hypoxia treatment groups. Hypoxia increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
5
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 37 publications
3
5
0
Order By: Relevance
“…The baseline values for the circulating MET-ENK plasma levels show the higher rnol wt forms of enkephalins (total MET-ENKi) predominant with mean baseline levels of 1755 versus 168 pg/mL for MET-ENKi (the low rnol wt peptides). The baseline values for norepinephrine and epinephrine levels were similar to data previously reported by our laboratory and others (16,17) and were believed to represent healthy, nonstressed animals.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…The baseline values for the circulating MET-ENK plasma levels show the higher rnol wt forms of enkephalins (total MET-ENKi) predominant with mean baseline levels of 1755 versus 168 pg/mL for MET-ENKi (the low rnol wt peptides). The baseline values for norepinephrine and epinephrine levels were similar to data previously reported by our laboratory and others (16,17) and were believed to represent healthy, nonstressed animals.…”
Section: Resultssupporting
confidence: 76%
“…Similar findings have been reported in human newborns (30). We have recently shown opiate receptor blockade with naloxone significantly augments epinephrine levels in fetal sheep exposed to hypoxia (17).…”
Section: Discussionsupporting
confidence: 74%
“…be low 10 Torr, would serve as a greater stimu lus to the opiate system. Our results are gen erally similar to those reported by Martinez et al [12], who failed to note any enhance ment of plasma E levels except following administration of low-dose (0.1 mg/kg) nal oxone. However, we did not observe any dif ference in response with the two doses (0.5 and 1.0 mg/kg) which we employed.…”
Section: Discussionsupporting
confidence: 81%
“…However, we did not observe any dif ference in response with the two doses (0.5 and 1.0 mg/kg) which we employed. Marti nez et al [12] have suggested that this doseresponse difference may reflect the approxi mately 10-fold greater affinity of naloxone for vasodepressant p-receptors over vaso pressor 8-receptors [22], Thus, naloxone at the lowest dose may more selectively block p-receptor-mediated inhibition of E release whereas this effect is masked at higher doses. However, this hypothesis conflicts with the observation of enhanced catecholamine re lease at birth in response to an even higher dose (2 mg/kg) of naloxone [16] than was employed in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation